Web 2.0 Students Adoption Model for Learning in Universities: A Case of Muni University, Uganda - Phelix, Businge Mbabazi; Nicholas, Nkamwesiga; Ritah, Nafuna; Patricia, Kyomugisha (International Journal for e-Learning Security (IJeLS), 2021)
The Web 2.0 is generally known as web technologies, tools, and software applications that support collaborative effort to create and share data [1]. Web 2.0 renders new teaching and learning technologies and can transform the way lecturers and students interact with each other and how students interact with others beyond four walls of the classroom. This study determined the students’ attitudes towards accepting the use of Web 2.0 Technologies for learning beyond the ordinary classroom. The Unified Theory of Acceptance and Use of Technology (UTAUT) model by Venkatesh et al. [2] was employed in this study to determine the strength of predictors for intention to accept and use Web 2.0 tools for teaching and learning. Questionnaires were administered to 100 students in the Faculty of Technoscience, Muni University. SPSS version 21 was used in data analysis. The results were presented in form of Tables, charts and means, percentages. P-values were used to predict the factors for the adoption of Web 2.0 in the process of teaching and learning in higher education. The results confirm several relationships in the UTAUT model as proposed by Venkatesh et al. [2] in predicting the behavioral Intention to use Web 2.0 for learning. The model shows that students’ behavioral intention to use Web 2.0 depends on performance expectancy, effort expectancy, social influence and facilitating conditions. The study also showed that students use YouTube, Facebook and Google Apps but not LinkedIn, Social Bookmarking, Moodle, Zoom, Edx, MIT Courseware, and Dropbox among others.